PENGARUH ALOKASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN LAMONGAN - Chodariyanti, Laily (Media Mahardhika, 2018)
This paper aims to find out the influence the allocation of Budget revenues and Shopping Regency (APBD) against the absorption of labor in Lamongan Regency. The methodology used is based secondary data from various official sources whereas the sample used was for the period 2007-2014. Data analysis tools applied in this study is a method of \the trend analysis and bivariate Correlation. The results of the analysis of the obtained answers that the absorption of labor in lamongan Regency will increase while the correlation between lamongan Regency Government spending with the absorption of labor in Lamongan Regency is very strong and direct.